Niche dynamics in amphitropical desert disjunct plants: Seeking for ecological and species‐specific influences. Issue 2 (26th November 2020) - Quiroga, R. Emiliano; Premoli, Andrea C.; Fernández, Roberto J.
Abstract: Aim: Numerous studies have assessed whether species niches are conserved in geographically separated regions. However, most of them were performed on invasive species, with the limitation that such species have likely not yet reached their potential distribution in the invaded region. Here we test the hypothesis of niche conservatism in the entire group of 25 amphitropical desert disjunct plant species, naturally distributed in North and South America but absent in the tropics. We also assessed the influence of ecological (intensity of biotic interactions) and species‐specific factors (dispersal ability and adaptation to stress) on species niche differentiation between the two continents. Location: North America and South America. Time period: Recent. Major taxa studied: Plants. Amphitropical desert disjunct species. Methods: Species' presence coordinates and five biologically relevant climatic variables were used to quantify niche differentiation of species between continents by means of principal component analysis. Then, structural equation modelling was performed to assess the influence on niche differentiation of proxies for intensity of biotic interactions (habitat net primary productivity), species dispersibility (dispersal mode and plant traits), and adaptation to stress (leaf size). Results: Niche shift was detected for 24 out of the 25 species, mostly towards cooler environments in South America (−2.5 °C average) with respect to North America. These niche shifts were best explained by the productivity of species' habitats, in particular by the displacement of species' niches away from the more productive and competitive environments of South America. Main conclusions: Niche shift seems to be the rule in amphitropical desert plants. Our findings highlight a previously undetected connection between amphitropical disjunct species and macroecological characteristics of the Americas. We show that prevalent environments differ between South and North America, and suggest that associated biotic contexts (mainly competition from widespread tropical and subtropical forests in South America) play a determinant role on species' distribution and niches.